Towards a Multimodal Pragmatic Analysis of Film Discourse in Audiovisual Translation - Mubenga, Kajingulu (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThis paper is about the introduction and use of Multimodal Pragmatic Analysis (MPA) as a research methodology in audiovisual translation (AVT). Its aim is to show the contribution of the MPA to the analysis of film discourse in AVT with a focus on interlingual subtitling. For this purpose, the paper is divided into five sections which elaborate on the theoretical and practical aspects of the MPA methodology. Following the introduction, the second section defines the context of MPA as a new research methodology in AVT at the level of approach, design and procedure. The third section describes the theoretical base of this methodology, and the fourth examines its basic components and levels of analysis. The fifth section provides two practical examples to show how the MPA methodology operates in the analysis of speech acts appearing in the source text and the target text. Finally, the last section first discusses the advantages and disadvantages of the methodology and then concludes the paper with some suggestions for further research.